RPP Bilingual dan Implementasinya Pada Pembelajaran IPAS Kelas IV Sekolah Dasar - Selasih, Mayang; Nuraini, Caryna; Karimah, Nisa Ul; Fajri, Luvensia Mei; Widagdo, Arif (Madani: Jurnal Ilmiah Multidisiplin, 2025)
In the era of globalization, the need for foreign language proficiency especially English is increasingly vital. Bilingual education has become a strategic approach implemented from the elementary school level to prepare the younger generation for global challenges. This article examines the implementation of bilingual Lesson Plans (RPP) using English and Indonesian in elementary education through a literature review approach. The findings show that bilingual learning offers various advantages, including improvements in students' linguistic, cognitive, and social abilities. However, challenges such as limited teacher competence, lack of resources, and students linguistic confusion still hinder effective implementation. This article also presents concrete solutions to address these obstacles and highlights the importance of collaboration among teachers, parents, and schools. Properly developed bilingual lesson plans can create a more effective, contextual, and adaptive learning process aligned with 21st-century needs.